Abnormal proplatelet formation and emperipolesis in cultured human megakaryocytes from gray platelet syndrome patients - Di Buduo, Christian A. (2016)
The Gray Platelet Syndrome (GPS) is a rare inherited bleeding disorder characterized by deficiency ofplatelet α-granules, macrothrombocytopenia and marrow fibrosis. The autosomal recessive form ofGPS is linked to loss of function mutations in NBEAL2, which is predicted to regulate granule traffickingin megakaryocytes, the platelet progenitors. We report the first analysis of cultured megakaryocytesfrom GPS patients with NBEAL2 mutations. Megakaryocytes cultured from peripheral blood or bonemarrow hematopoietic progenitor cells from four patients were used to investigate megakaryopoiesis,megakaryocyte morphology and platelet formation. In vitro differentiation of megakaryocytes wasnormal, whereas we observed deficiency of megakaryocyte α-granule proteins and emperipolesis.Importantly, we first demonstrated that platelet formation by GPS megakaryocytes was severelyaffected, a defect which might be the major cause of thrombocytopenia in patients. These resultsdemonstrate that cultured megakaryocytes from GPS patients provide a valuable model to understandthe pathogenesis of GPS in humans.